2022
DOI: 10.1155/2022/6596702
|View full text |Cite
|
Sign up to set email alerts
|

The Application of [68Ga]‐Labeled FAPI‐04 PET/CT for Targeting and Early Detection of Pancreatic Carcinoma in Patient‐Derived Orthotopic Xenograft Models

Abstract: [18F]FDG as a probe of PET/CT is a radiolabeled glucose analogue taken up by most cells, but its batch activity is limited. [68Ga]FAPI-04 is a promising alternative based on a fibroblast activation protein-specific inhibitor (FAPI) labeled with radiotracer FAP. Here, a series of databases suggested that FAP expression was significantly different in pancreatic cancer compared to normal tissue. The FAP-positive fibroblasts were evaluated around the tumor cells and the stroma. A patient-derived orthotopic xenogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…We noted two instances where diffuse 18 F-FAPI-04 uptake occurred due to tumor-associated pancreatitis, which could potentially cause an overestimation of tumor volume. Guided by prior research [ 16 ], we executed an additional 2-hour delayed 18 F-FAPI-04 PET/CT scan to aid in differential diagnosis. The results from these dual-time scans showed differential kinetics between tumor-associated pancreatitis, which had decreased uptake, and pancreatic cancer, which demonstrated stable uptake.…”
Section: Discussionmentioning
confidence: 99%
“…We noted two instances where diffuse 18 F-FAPI-04 uptake occurred due to tumor-associated pancreatitis, which could potentially cause an overestimation of tumor volume. Guided by prior research [ 16 ], we executed an additional 2-hour delayed 18 F-FAPI-04 PET/CT scan to aid in differential diagnosis. The results from these dual-time scans showed differential kinetics between tumor-associated pancreatitis, which had decreased uptake, and pancreatic cancer, which demonstrated stable uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies in mouse models of PDAC showed significant growth delay after a single injection of 225 Ac-FAPI-04, further supporting its potential as a therapeutic agent [108]. FAPI-04 ( 68 Ga-FAPI) was also used to detect early lesions in an orthotopic model of PDAC, using PDXs tumors [109]. This molecule was also labeled with 131 I and 211 At for PRRT in gliomas.…”
Section: Development Of β-And α-Emitter Labeled Fapismentioning
confidence: 93%
“…Continued development of these promising compounds has led to multiple preclinical studies, providing data to support the further translation of these compounds. One such study evaluated the potential of 68 Ga-FAPI-04 PET imaging in patient-derived pancreatic cancer xenografts, finding that 68 FAPI-04 displayed superior tumor-to-background uptake than 18 FDG-PET [182]. Another study evaluated the theranostic combination of 64 Cu-FAPI-04 and 225 Ac-FAPI-04, demonstrating excellent tumor targeting, although in most organs 64 Cu-FAPI-04 accumulation was significantly higher than 68 Ga-FAPI-04, suggesting that the latter may be superior for FAP PET imaging.…”
Section: Fapimentioning
confidence: 99%